Prospective observational comparative study of outcomes between single-layer versus double-layer gastrointestinal anastomosis - Md Hakim Mia,; Kuiri, Shib Shankar; Kanchan Kundu,; Sayan Chakrabarty, (Asian Journal of Medical Sciences, 2023)
Background: In elective gastric surgeries, gastrojejunostomy is the most common anastomosis being done in both benign and malignant conditions. Anastomotic leak, bleeding, wound infection, and anastomotic stricture are important complications associated with intestinal anastomosis. Both double-layer and single-layer anastomosis are well-established techniques for gastrojejunostomy. Till now, there are no definite concluding findings that determine the suitability of either technique. Aims and Objectives: To compare the utility of single-layer gastrointestinal anastomosis versus double-layer gastrointestinal anastomosis in terms of post-operative outcome. Materials and Methods: A hospital-based prospective comparative study was conducted in the department of general surgery BSMCH with a time frame of about 1/2 years. A total no of 52 patients of the adult age group (18–80 years) admitted in the department of general surgery underwent gastrointestinal anastomosis has been studied. Results: Twenty-six (50%) patients underwent single-layer gastrointestinal anastomosis. The rest 26 (50%) underwent double-layer anastomosis. There is no statistically significant difference between these two groups in terms of post-operative nausea vomiting (P=0.73419), wound infection (P=0.385332), anastomotic leak (P=0.552003), and pelvic abscess (P=0.4924). However, the duration of surgery (P<0.0001) and hospital stay (P=0.0179) was significantly less in single-layer gastrointestinal anastomosis. Conclusion: Double-layer gastrointestinal anastomosis offers no definite advantage over single-layer anastomosis in terms of post-operative complications. Considering the duration of the anastomosis procedure and hospital stay, single-layer gastrointestinal anastomosis may prove the optimal choice in most surgical situations.